Membangun Ekosistem E-Commerce Yang Mendukung Pertumbuhan UMKM: Peluang Dan Tantangan di Masa Depan - Raissha Vathyma Azzahra; Muhammad Irwan Padli Nasution (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This article discusses the importance of building an e-commerce ecosystem that supports the growth of Micro, Small and Medium Enterprises (MSMEs). In an era of increasingly rapid digitalization, MSMEs need to adopt e-commerce platforms to expand their market reach and increase their competitiveness. However, to achieve sustainable growth, a strong and sustainable e-commerce ecosystem needs to be built. In this article, the author identifies the opportunities that exist in building an e-commerce ecosystem that supports MSMEs. One of the main opportunities is access to a wider global market, which can open the door for MSMEs to sell their products to customers around the world. In addition, e-commerce platforms also provide opportunities for MSMEs to utilize new technologies such as artificial intelligence and data analytics to improve operational efficiency and decision making.